Review of the book "Orientamento educativo e professionale" - Ferraro, Speranzina (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The book ‘Educational and Career Guidance: Theories, Practices and Research’ by Lorenza Da Re, published by PENSA Multimedia, is the result of and completes the fruitful reflection on the subject that developed during the study seminar held online on 6 October 2023. The text addresses the theme of guidance, which is central to the current historical moment, highlighting both its great pedagogical history and the polysemic richness it brings with it, while also emphasising its continuous and fertile evolution, linked to the complexity of the times we live in. The book consists of three parts. The first part, which serves as a framework and background, outlines the pedagogical trajectories of educational guidance from the last century to the present day, with particular attention to developments in our country. The second and third parts contain specific and thematic insights, together with experiences, practices and research in the field of guidance. The book offers an opportunity to reflect on guidance and the development of this concept, especially with regard to educational and professional guidance towards informed choices for the future.